2010
DOI: 10.1007/s10230-010-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phototrophic Biomass on Fe and S Redox Cycling in an Acid Mine Drainage-Impacted System

Abstract: We examined the effects of organic carbon from oxygenic photosynthetic algal biomass on the redox cycling of Fe and S in an acid mine drainage (AMD)-impacted system. Fe(III)-rich sediments from the field site with abundant algae contained fewer Fe(II) oxidizing bacteria and lower rates of Fe(II) oxidation compared to sediments that did not contain abundant algae. The addition of algal biomass to sediments that did not previously contain abundant algae inhibited microbiological Fe(II) oxidation and enhanced mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…A variety of phototrophic microeukaryotes may be present in AMD-impacted setting (Rowe et al, 2007; Sánchez España et al, 2007; Senko et al, 2011), including Euglena mutabilis (Brake et al, 2004; Aguilera et al, 2007; Brake and Hasiotis, 2010), which was the most abundant phototrophic microeukaryotic phylotype detected in the sediments (Figure 5, Table 2). Notably, the abundance of phototrophic microeukaryotic phylotypes was coincident with relatively high DO concentration (Figures 1, 4).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of phototrophic microeukaryotes may be present in AMD-impacted setting (Rowe et al, 2007; Sánchez España et al, 2007; Senko et al, 2011), including Euglena mutabilis (Brake et al, 2004; Aguilera et al, 2007; Brake and Hasiotis, 2010), which was the most abundant phototrophic microeukaryotic phylotype detected in the sediments (Figure 5, Table 2). Notably, the abundance of phototrophic microeukaryotic phylotypes was coincident with relatively high DO concentration (Figures 1, 4).…”
Section: Resultsmentioning
confidence: 99%
“…Das et al (6) highlighted the significance of eukaryotic microorganisms in mine waters and alluded to the possible role of algae in sustaining populations of SRB. More recently, Senko et al (25) have provided evidence for the role of algae in enhancing iron reduction in AMD environments. Oxygen evolution by acidophilic algae can also influence iron and sulfur cycling and was probably the reason why ferric iron precipitates accumulated immediately below the algal surface layer in TV mesocosms (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the solid phases from uninoculated media by XRD suggested that the predominant mineral in all cases was schwertmannite (Fig. 2B, D, and F) (5,6,58). XRD analysis of the solid phases recovered from the GBSRB4.2 cultures that were amended with 1 Fe(II):0 Fe(III) suggested the presence of mackinawite (FeS) and greigite (Fe 3 S 4 ), a ferrimagnetic FeS phase ( Fig.…”
Section: Growth and Activities Ofmentioning
confidence: 95%